Synthesis of novel carbazole hydrazine-carbothioamide scaffold as potent antioxidant, anticancer and antimicrobial agents (vol 18, 102, 2024) - Capan, Irfan; Hawash, Mohammed; Qaoud, Mohammed T.; Gueluem, Levent; Tunoglu, Ezgi Nurdan Yenilmez; Cifci, Kezban Ucar; Tutar, Yusuf (Bmc, 2024)
[Abstract Not Available]